Verloskundige Verpleegkunde ... 'n Uitdaging - S. Venter (AOSIS, 1978)
Much has been achieved through the advances of medical science and technology and that calls for improved knowledge and skills for today's midwife. There is hardly a sphere in midwifery practice that can't be seen as a challenge for the midwife, for instance as a administrator; as a tutor; as a clinician and a researcher. In the performance of her task certain challenges are placed upon the midwife as person, for instance the challenge as counsellor; communicator; as a member of the health team; as a member of the changing community and as a family planner. Inservice training and continuing education are therefore a necessity to ensure a high standard of midwifery care.